Digital payment systems and the speed of public sector employee pension payout in South Africa - Masipa, Mafolelo (University of the Witwatersrand, Johannesburg, 2024)
The study seeks to investigate factors affecting pension fund payout delays in the Gauteng Province with a view to exploring the effect of digitalisation as a possible solution. The study focuses on pensions related to government employees in South Africa, specifically pension fund administration by the Government Employee Pension Fund (GEPF). The processing of pension claims by GEPF utilises a semi- digitised pension case management system to process pension payouts. The system was introduced as an intervention to complaints raised by members regarding delays in pension payouts. The objective of the study was to investigate various aspects of the GEPF payment process to determine the factors responsible for payout delays and the possible implications of digitalisation. The study explores frameworks related to digitalisation through a qualitative research approach. Data was collected using a semi-structured questionnaire from employees in the administrative sector of the GEPF. The data derived from employee responses was analysed for common emerging themes using content analysis. Key findings show that delays in pension pay-outs were caused by errors or inaccuracies from the GEPF members or their employers, which digitalisation has the potential to mitigate. These key findings are supported by the global 2030 Sustainable Development Agenda, which advocates for broad-scale digital transformation in order to promulgate the worldwide Sustainable Development Goals. The majority of the respondents concurred that digitalisation of the GEPF system appears to satisfy all these constructs and in so doing provides a framework for alleviating the problem of pension payout delays.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Digital payment systems; Digital payments; Pension fund payout delays; Digitalisation of pension fund administration; Speed of payment; UCTD; SDG-8: Decent work and economic growth